Strategi Pengembangan Kelembagaan Penyediaan Layanan Internet dalam Komunitas dan Desa Digital (Studi di Badan Usaha Milik Antar Desa Panca Mandala Kabupaten Tasikmalaya) - Meilandi, Irman; M Kolopaking, Lala; P Lubis, Djuara (Departement of Communication and Community Development Sciences, Faculty of Human Ecology, 2022)
Bumades Panca Mandala which was established by the Inter-Village Cooperation Agency is an institution for providing internet access for villages in Jatiwaras District, Tasikmalaya Regency. The activities are carried out through a partnership program with a company as an Internet Service Provider and the Telecommunication and Information Accessibility Agency (BAKTI). This study aims to analyze the development process, identify the level of development, and formulate an institutional development strategy for providing internet services. To fulfill the purpose, qualitative research is used which is supported by quantitative data analysis. The research location is in 5 villages that are members of the Panca Mandala Inter-Village Cooperation Agency in Tasikmalaya Regency, West Java Province. The research was carried out from July 2019 to July 2021. Data collection was carried out using various techniques. Group interviews and in-depth interviews were conducted with informants consisting of community leaders, village government, youth, farmers, traders, and ranchers from the villages of Mandalamekar, Mandalahurip, Papayan, and Kertarahayu. The questionnaires were distributed to 30 respondents managing PT Bumades Panca Mandala. Focus Group Discussion and Technology Participation facility methods were carried out to formulate the institutional development strategy. The research findings indicate that the process of developing internet access provision requires the form of a business entity. The results of this process have connected the internet in 23 village offices, 4 schools, 21 MSMEs, and 52 households. In addition, the process has opened up new job opportunities for village youth. The level of progress of PT Bumades Panca Mandala as an internet provision institution in the village is in the Developed category. To maintain the increase in development, a progressive strategy is formulated, namely overcoming weaknesses to take advantage of opportunities and challenges in providing internet infrastructure in digital community development-based villages.